99 Pulmonary vein isolation for atrial fibrillation: ice 'block' vs ring of fire. (4th June 2021) - Reddy, Ashwin; Nethercott, Sarah; Khialani, Bharat; Virdee, Munmohan
Abstract : Background: Over the last 20 years various techniques have been developed striving for safer and more durable pulmonary vein isolation (PVI). The popularity and uptake of 'single-shot' strategies, which by their nature are simpler and quicker, has risen in line with the growing worldwide prevalence of AF and the concomitant requirement to simplify and streamline AF ablation service delivery. The most commonly used single-shot techniques are pulmonary vein ablation catheter (PVAC) and cryoballoon. Head-to-head assessment of outcomes of new-generation cryoballoon vs PVAC gold has never before been performed. Objective: Evaluate the safety and efficacy of PVAC gold vs cryoballoon in an unselected population undergoing de-novo ablation for persistent or paroxysmal atrial fibrillation (AF) at Royal Papworth Hospital (RPH). Method: Retrospective, single-centre study of consecutive AF ablations at RPH over a one year period. Demographic, procedural and outcome data were analysed. Complications were defined as any adverse procedure-related event. Success was defined as freedom from symptoms or demonstrable arrhythmia after 12 months following an initial 3-month blanking period. The consultant performing the procedure determined the ablation method used. Cases performed using point-by-point techniques or AcQMap were excluded from analysis. Analysis of parametric continuous data were performed using Student's t-tests, whilst categorical data were compared using the χ2 test. A two-tailed probability level of <0.05 was considered significant. Paroxysmal and persistent AF groups were examined separately due to the well-recognised differences in long-term outcome between the two entities. Results: Over the study period 329 first-time PVI procedures were performed. 131 (39.8%) were performed using cryoballoon (106 [78.6%] of which were for pAF) and 75 (22.8%) using PVAC (62 [82.7%] for pAF). The average age was 60.4 ± 10 years and 69.6% of patients were male. There was no significant difference in age, sex, left atrial diameter or cardiovascular co-morbidity profile between different ablation technique groups ( table 1 ). Procedure times were similar between interventions (127 vs 117 mins, p=0.79). Acute vein isolation was achieved in 96.9% of cryoballoon patients and 98.7% of PVAC patients (p=0.88). 12-month freedom from symptomatic AF was not significantly different between cryoballoon and PVAC (75.7 vs 78.6%, p=0.99 for paroxysmal AF; 75.0% vs 83.3%, p=0.80 for persistent AF) ( figure 1 ). Overall complication rate was 1.9%, and similar between groups ( table 2 ). A pseudoaneurysm occurred following a PVAC case requiring surgical intervention. One case each of phrenic nerve palsy, right leg numbness (due to local infiltration of local anaesthetic around the femoral nerve) and air embolism were associated with cryoablation. All resolved within hours, did not require intervention and did not delay discharge. No long-term sequelae were seen. Conclusions: PVAC and cryoballoon AF ablation appear equally efficacious with similar procedure times in an unselected population. Both were associated with a low adverse event rate. Conflict of Interest: nil